2005
DOI: 10.1093/ajcn/81.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of multifrequency bioelectrical impedance analysis with dual-energy X-ray absorptiometry for assessment of percentage body fat in a large, healthy population

Abstract: BIA is a good alternative for estimating %BF when subjects are within a normal body fat range. BIA tends to overestimate %BF in lean subjects and underestimate %BF in obese subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
211
4
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(257 citation statements)
references
References 31 publications
29
211
4
7
Order By: Relevance
“…In that study, Ebbeling et al (44) found that those assigned to receive non-caloric beverage provisions for 1 year had smaller gains in BMI compared with those assigned to the control group. Interestingly, body fat did not relate to the experimental condition, but it was obtained by bioelectrical impedance (as opposed to DXA as in our study), which has been shown to inaccurately measure body fat in overweight individuals (45) .…”
Section: Discussioncontrasting
confidence: 65%
“…In that study, Ebbeling et al (44) found that those assigned to receive non-caloric beverage provisions for 1 year had smaller gains in BMI compared with those assigned to the control group. Interestingly, body fat did not relate to the experimental condition, but it was obtained by bioelectrical impedance (as opposed to DXA as in our study), which has been shown to inaccurately measure body fat in overweight individuals (45) .…”
Section: Discussioncontrasting
confidence: 65%
“…In this study, body composition was assessed with BIA, a method that may be less precise in overweight adults. 24 In addition, the study length was possibly too short for an effect to be observed. A commonality among the three remaining studies in overweight adults that did not find an effect of CLA on body fat was the inclusion of a weight loss component: Whigham et al 13 included a 12-week very low-calorie diet (VLCD); Kamphius et al 12 utilized a 3-week VLCD; and Atkinson 7 included a diet and exercise regimen during 6 months of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…BMI (kg m À2 ) was calculated as body weight/(estimated height) 2 . Body composition (fat mass) was measured, for patients able to stand up, by using the Tanita DC-320 (Tanita Corp., 232 Tokyo, Japan) BIA device based on four separate foot-pad electrodes mounted on the system's base, 21 with subjects in indoor clothing and no shoes.…”
Section: Collection Of Baseline Datamentioning
confidence: 99%